Aplikasi Kinerja Pembangkit Listrik Tenaga Surya 1200 WP Terhadap Beban Pompa Air Menggunakan Homer Pro Di Desa Pandan Arang - Ardianto, Feby; Alfarezi, Bengawan; Taufik, Taufik; Aziz, M. Wisyah (Universitas Batanghari Jambi, 2023)
Pandan Arang Village is located in Ogan Komering Ilir District, Kandis District, South Sumatra Province. Solar energy potential in this village is 4.95 kWh/m2/day. Utilization of alternative energy by building a Solar Photovoltaic (PLTS) system. The research aims to analyze the performance of a 1200 WP solar power plant with a water pump load of 2226 kW. The research method consists of 4 stages: 1. Location survey, 2. Data collection, 3. Simulation, 4. Technical analysis. Location data collection includes PLTS components and load data. This data is used for simulations using the HOMER PRO application. The simulation results show that the amount of electrical energy produced is 1605 kWh/year or 4.4 kWh/day. Simulation with 2 water pump loads produces unused electrical power of 3574 kWh/year or 72% of the total annual load. Meanwhile, in the simulation, the unused electricity load for 1 water pump is 1092 kWh/year. Thus, it can be concluded that the 1200 Wp PLTS system cannot meet the daily electricity load requirements for a year.